Waste Bank Digitalization: Towards a Waste-Free Meruya Selatan Village: Digitalisasi Bank Sampah: Menuju Kelurahan Meruya Selatan Bebas Sampah - Alfia, Yulis; Rahayu, Puji; Bernadetha Stephani, Suzan (Universitas Lancang Kuning, 2025)
This Community Service activity aims to improve the effectiveness of waste bank management through a mobile-based application in Meruya Selatan Village. A participatory action research approach is used to design and implement applications that can improve transparency, efficiency, and effectiveness of management through community involvement. The involvement starts from the planning and design stages of the application system. Socialization activities were part of the pre-implementation activities aimed at exploring user knowledge and capabilities, as well as evaluating the pre-design of the system. The survey results confirmed the level of intention to use gadgets among the community, the importance of 4R education, and the need for scheduling waste pickup to support the effectiveness of waste bank management. The evaluation results were analyzed and used as the basis for developing business process system designs and digital applications as part of the action of this PKM program. The expected contribution of this activity is the formation of an appropriate management digitization system that can be used by the community in answering the objectives of economic and environmental benefits.